PBG 1. Genetic Diversity Analysis and Ecotilling in coconut ( Cocos nucifera L.) for host insect Resistance (The Philippine Journal of Crop Science, 2018)
Using a core-set of germplasm from the Philippine Coconut Authority (PCA) genebank, the genetic diversity of 73 coconut (Cocos nucifera L.) varieties was analyzed using 16 microsatellite (SSR) markers mapped from each coconut chromosome. The sampled germplasm represents the Tall, Dwarf and Hybrids collections of the PCA including recommended varieties. For host insect resistance, the same set of coconut germplasm was analyzed for natural allele variants targeting plant glandular trichome and host insect resistance-associated genes. The overall outcome of the population genetic cluster analysis supports the distinct ecotype classification of coconut based on probable area of origin– the Indo– atlantic and the Indo– Pacific coconuts; as well as the country/region of cultivation or germplasm source. Results from the study also support the concept that dwarf varieties were domesticated from Tall population, but whether the Pacific Region was indeed the center of coconut domestication is yet to be determined using more in-depth molecular, morphology and socio-cultural evidences. On the other hand, PCR conditions were optimized to mine the natural variants of identified genes associated with glandular trichomes and host insect resistance through Targeting Induced Local Lesions in Genomes (EcoTILLING). Natural SNPs on coronatine-insensitive 1 (COI 1) loci were characterized, while 10 other candidate genes are being screened. The statistical association of these SNP markers to coconut trichome trait and non-preference against coconut scale insect (CSI) is being analyzed. Validated SNPs and underlying genes will be further characterized, and mechanism elucidated, for later deployment in genomics-assisted coconut breeding for outstanding and insect resistant coconut varieties.